Study of Electrical System Analysis of Instructor Dormitory Type 54 of West Sumatera Shipping Polytechnic - Hanafi, Raka Putra; Ridal, Yani; Rauf, Rosnita (Dinasti International Journal of Digital Business Management, 2025)
Electrical installation is a vital component in supporting the function and operation of a building, especially in residential facilities such as dormitories. Installations that do not meet standards can cause various problems such as power outages, overloading, and potential fire hazards. This study aims to analyze the electrical system in the Type 54 Dormitory Instructor of the West Sumatra Shipping Polytechnic based on the Indonesian National Standard (SNI) and General Requirements for Electrical Installations (PUIL) 2011. The results of the analysis show that the total installed power is 106,992 Watts using a 3-phase MCCB 224-320A with an incoming cable size from LVMDP NYY 4 x 120 mm². The incoming electrical power from PLN is 82.5 kVA (125A). DP.PLT 1 total load is 35,664 Watts using a 3-phase MCCB 100A with a cable size of NYY 4 x 25 mm². DP.PLT 2 total load of 35,664 Watts using 3-phase 100A MCCB with NYY cable size 4 x 25 mm². DP.PLT 3 total load of 35,664 Watts using 3-phase 100A MCCB with NYY cable size 4 x 25 mm². Although the installation has been running, the results of the study show that the electrical system has not fully met the criteria for reliability, safety, and energy efficiency. Therefore, evaluation and improvement of the system are needed to ensure safe and sustainable operational continuity.